2007
DOI: 10.1109/tpami.2007.1129
|View full text |Cite
|
Sign up to set email alerts
|

From Scores to Face Templates: A Model-Based Approach

Abstract: Regeneration of templates from match scores has security and privacy implications related to any biometric authentication system. We propose a novel paradigm to reconstruct face templates from match scores using a linear approach. It proceeds by first modeling the behavior of the given face recognition algorithm by an affine transformation. The goal of the modeling is to approximate the distances computed by a face recognition algorithm between two faces by distances between points, representing these faces, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…Most of the face reconstruction methods have been experimented in this context (e.g. [1,2,21]), explaining why they observed that simple gradient based optimization allows to reconstruct faces easily in their cases.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the face reconstruction methods have been experimented in this context (e.g. [1,2,21]), explaining why they observed that simple gradient based optimization allows to reconstruct faces easily in their cases.…”
Section: Related Workmentioning
confidence: 99%
“…However, as pointed out by [21], this hill-climbing optimization is rather inefficient as it involves the optimization of a non-convex criterion and requires a large number of attempts before succeeding. Consequently, [21] proposed to use a different paradigm.…”
Section: Related Workmentioning
confidence: 99%
“…The stress on linearity is not just based on appeal to Occam's razor, but also because of possible impact on template security, privacy, indexing. In [11] we have shown that if we can build globally linear models of the distances, then it is possible to construct approximating linear models that map biometric templates to distances, as computed by a recognition algorithm. Based on this linear model, it is possible to reconstruct any target template given just the similarity scores of this target template with a set of break-in query templates.…”
Section: Pranab Mohanty Was With University Of South Florida and Is Nmentioning
confidence: 99%
“…In [2] a model-based attack which is capable of reconstructing the user's face images from the matching scores is presented. The method has the strong constraint of needing a large number of real face images to initialize the algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing works studying the vulnerabilities of biometric systems to attacks against the inner modules of the system, apart from [2], use some type of variant of the hillclimbing algorithm presented in [3]. Some examples include an attack to a face-based system in [4], and to a standard and a Match-on-Card minutiae-based fingerprint verification systems in [5] and [6] respectively.…”
Section: Introductionmentioning
confidence: 99%